Analisis kinerja PT Bank Syariah Indonesia Tbk melalui pendekatan Balanced Scorecard - Kurniawan, Pandu; Sharunh, Mohammad Rizna; Saputra, Aditya Gilang; Shafrani, Yoiz Shofwa (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
The Balanced Scorecard (BSC) approach enables a more holistic performance evaluation by considering non-financial aspects as equally important as financial indicators. Findings from this study indicate that PT Bank Syariah Indonesia Tbk (BSI) has not only achieved strong financial performance following the merger, but has also demonstrated significant progress in other strategic dimensions. From the financial perspective, BSI recorded solid profitability with an average Net Profit Margin (NPM) of 25.01%, Return on Assets (ROA) of 2.27%, and Return on Equity (ROE) of 17.16%, consistently exceeding the national banking industry average. In the customer perspective, the increase in the number of customers—reaching over 20 million by mid-2024—reflects BSI’s success in building customer loyalty and satisfaction, including through digital service innovations and enhanced banking accessibility. From the internal business process perspective, operational efficiency has continued to improve, as evidenced by the declining BOPO ratio, strengthened information technology systems, and strategic expansion through the opening of a branch in Dubai as a first step toward the international stage. Meanwhile, in the learning and growth dimension, BSI has shown a strong commitment to human resource development through training and skill enhancement, reinforcement of a work culture based on the core values of AKHLAK (Trustworthy, Competent, Harmonious, Loyal, Adaptive, and Collaborative), and digital transformation through the launch of the BYOND by BSI SuperApp. By consistently integrating all four BSC perspectives, BSI has not only enhanced its overall performance but also strengthened its foundation for long-term growth. The BSC approach has proven to be a strategic and effective tool for comprehensively, sustainably, and adaptively evaluating and directing the performance of Islamic financial institutions in an evolving landscape.